INTEGRATING ESG AND MAQASHID SHARIAH IN ISLAMIC INVESTMENT FOR ECONOMIC SUSTAINABILITY: A SYSTEMS APPROACH BY JASSER AUDA - A'yun, Inarotul; Sollaini, Sollaini; Muslim, Dzurotun Khanifah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to examine the integration of Environmental, Social, and Governance (ESG) principles with the maqashid sharia in Sharia investment practices and their contribution to economic sustainability. The method employed is a Systematic Literature Review (SLR) utilizing Jasser Auda’s systemic approach, which facilitates multidimensional, contextual, and adaptive analysis of global challenges. The research process was conducted through the stages of formulating research questions, searching literature from various international and national databases, selecting articles using inclusion criteria, and analyzing using the PRISMA 2020 flowchart. Of the total 109 articles searched, 5 were chosen as relevant primary data for further analysis. The results show that the integration of ESG and maqashid sharia provides a strong conceptual foundation for realizing sustainable sharia investment. ESG provides technical standards that emphasize environmental preservation, social responsibility, and good governance, while maqashid sharia presents normative and spiritual legitimacy oriented towards human welfare. The impact of this integration includes the formation of an inclusive, resilient, and long-term investment ecosystem, as well as the development of relevant instruments, such as green sukuk, increased transparency of governance, and strengthened distributional justice and environmental protection.